2016
DOI: 10.1016/j.aim.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Non-semi-simple TQFTs, Reidemeister torsion and Kashaev's invariants

Abstract: Abstract. We construct and study a new family of TQFTs based on nilpotent highest weight representations of quantum sl(2) at a root of unity indexed by generic complex numbers. This extends to cobordisms the non-semi-simple invariants defined in [12] including the Kashaev invariant of links. Here the modular category framework does not apply and we use the "universal construction". Our TQFT provides a monoidal functor from a category of surfaces and their cobordisms into the category of graded finite dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(99 citation statements)
references
References 48 publications
(107 reference statements)
1
98
0
Order By: Relevance
“…Finally, the category U q sl(2)-mod is not semi-simple nor braided and has an infinite number of non-isomorphic simple modules. However, one can easily modify U q sl(2) and obtain a braided category of highest weight modules which has been used to construct invariants of links [24], of 3-manifolds [8] and TQFTs [4]. The aim of this paper is to give an overview of the algebraic results related to this modified quantization and prove a few straightforward results.…”
Section: A Quantization Of Sl(2) and Its Associated Ribbon Categorymentioning
confidence: 97%
See 3 more Smart Citations
“…Finally, the category U q sl(2)-mod is not semi-simple nor braided and has an infinite number of non-isomorphic simple modules. However, one can easily modify U q sl(2) and obtain a braided category of highest weight modules which has been used to construct invariants of links [24], of 3-manifolds [8] and TQFTs [4]. The aim of this paper is to give an overview of the algebraic results related to this modified quantization and prove a few straightforward results.…”
Section: A Quantization Of Sl(2) and Its Associated Ribbon Categorymentioning
confidence: 97%
“…We also study the decomposition of the tensor product of certain indecomposable modules (see Section 8). These results are used in [4] in an essential way to build a TQFT for 3-manifolds equipped with a cohomology class. The category U H q sl(2)-mod contains some indecomposable non-projective modules that are not studied in this paper (see for example their use in [9]).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In particular, when = 4 and g = sl(2) in [5] it is shown that the closed 3-manifold invariant of [8] associated to the category C H sl(2) are a canonical normalization of Reidemeister torsion defined by Turaev which gives rise to a Topological Quantum Field Theory (TQFT). It would be interesting to see what properties the analogous topological invariants have for other Lie algebras at similar level.…”
Section: Conjectures For Quantum Groups At Even Ordered Roots Of Unitymentioning
confidence: 99%